Nanocarbon-Edge-Anchored High-Density Pt Atoms for 3-nitrostyrene Hydrogenation: Strong Metal-Carbon Interaction - Lou, Yang; Wu, Honglu; Liu, Jingyue (iScience, 2019)
Strong metal-support interaction (SMSI) has been widely used to improve catalytic performance and to identify reaction mechanisms. We report that single Pt atoms anchored onto hollow nanocarbon (h-NC) edges possess strong metal-carbon interaction, which significantly modifies the catalytic behavior of the anchored Pt atoms for selective hydrogenation reactions. The strong Pt-C bonding not only stabilizes single Pt atoms but also modifies their electronic structure, tunes their adsorption properties, and enhances activation of reactants. The fabricated Pt1/h-NC single-atom catalysts (SACs) demonstrated excellent activity for hydrogenation of 3-nitrostyrene to 3-vinylaniline with a turnover number >31,000/h, 20 times higher than that of the best catalyst for such selective hydrogenation reactions reported in the literature. The strategy to strongly anchor Pt atoms by edge carbon atoms of h-NCs is general and can be extended to construct strongly anchored metal atoms, via SMSI, onto surfaces of various types of support materials to develop robust SACs. [Display omitted] •A strategy is proposed to anchor metal atoms to edge carbon atoms of graphene sheets•Formation of Pt1-C bond tunes performance of Pt1/h-NC single-atom catalyst (SAC)•Pt1/h-NC SAC is 20 times more active than the best catalyst for 3-nitrostyrene hydrogenation•Electronic SMSI can be effectively used to tune catalytic properties of SACs Chemical Reaction Engineering; Catalysis; Nanostructure